Exploring social media adoption in small and medium enterprises in Iraq: pivotal role of social media network capability and customer involvement - Hussam Al Halbusi (14492861) (2022)
Small and Medium-sized Enterprises (SMEs) can communicate with their consumers and provide them with relevant information on cost-effective goods or services with the help of social media technologies. Thus, this study investigated the factors influencing social media technologies on SMEs’ performance. In addition, this study also tests the capability of social media networks and customer involvement to enhance the positive effect of social media usage. The data was collected from 253 SMEs. Our results show that cost-effectiveness, compatibility, and interactivity, were positively related to social media usage. However, trust was not significantly related to the use of social media. Notably, the positive effect of social media usage and SMEs’ performance was positively moderated by the capability of the social media networks and customer involvement. The relationship was more robust when social media capability and customer involvement were high than low. Therefore, this study has highlighted the role of social media usage, customer involvement, and social media capability and their effect on SMEs’ performance. Other Information Published in: Technology Analysis & Strategic Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/09537325.2022.2125374